ANALISIS PENDAPATAN USAHA ABON IKAN TENGGIRI PADA INDUSTRI RUMAH TANGGA â€œALTHAF FOODâ€DI KOTA PALU - Nur Syafar,Arifuddin Lamusa, Moh (AGROTEKBIS, 2015)
Fish is quickly undergoing spoiled. Therefore the community process fish to several alternatives forms such as fish floss. Home industry ?Althaf Food? produces fish floss from mackerel. Located in ulujadi sub-district Palu City.The purpose of this study was to analyse the income of ?Althaf Food?. The owner and employee from the production department were selected as respondents. The income was analysed from the interview data. The study showed that the ?Althaf Food? produces fish floss got income amounting to 1,638,612 IDR in four times of a month.